2011
DOI: 10.1097/mco.0b013e328341368c
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amino acid imbalance: dangerous in chronic diseases?

Abstract: Recent investigations revealed that amino acids are powerful molecules in mediating cell signalling. Therefore, it can be hypothesized that the severe amino acid imbalances as observed in uraemia or liver failure may exert a relevant impact on various physiologic processes and on organ function. The recent results described in Drosophila should stimulate a new research area on the effect of amino acid supply in various disease processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…In C. elegans nematodes free amino acid concentrations change with age [ 1 ] and are altered in long-lived worms [ 2 ]. In humans, altered plasma amino acid concentrations are biomarkers of several diseases [ 3 ] such as type 2 diabetes [ 4 ]. Calorie restriction has long been known to delay aging [ 5 ] and protein restriction may be responsible for around half of this effect [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In C. elegans nematodes free amino acid concentrations change with age [ 1 ] and are altered in long-lived worms [ 2 ]. In humans, altered plasma amino acid concentrations are biomarkers of several diseases [ 3 ] such as type 2 diabetes [ 4 ]. Calorie restriction has long been known to delay aging [ 5 ] and protein restriction may be responsible for around half of this effect [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the human body, plasma amino acid imbalances occur in various diseases, and such imbalances may exert specific negative effects on various physiological processes and organ functions 1 . Several recent studies have demonstrated a strong correlation between alterations in the concentrations of various plasma free amino acids (PFAAs) and the development of lifestyle-related diseases (LSRDs), including diabetes mellitus (DM), dyslipidemia, hypertension and metabolic syndrome (MetS) 2 – 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Heute sollen nur Lösungen verwendet werden, die essenzielle und nicht essenzielle AminosĂ€uren entweder in einem Standardmuster oder in einer spezifisch an den bei Niereninsuffizienz gestörten Metabolismus orientierten Zusammensetzung enthalten. In Anbetracht neuerer Untersuchungen zu Funktionen von AminosĂ€uren, die weit ĂŒber den Proteinhaushalt hinausgehen, wie intrazellulĂ€res Signalling im mTOR-Weg, dĂŒrften spezielle Lösungen in Zukunft wieder verstĂ€rkt diskutiert werden [23].…”
Section: Empfehlungunclassified